Legal Certainty in Money Laundering Prosecutions in Indonesia: A Focus on Corruption as a Predicate Crime Tofik Yanuar Chandra - Tofik Chandra (Lex Publica, 2018)
The offense of money laundering is intrinsically linked to a prior criminal act, known as a predicate crime, as the assets involved, whether placed, transferred, or integrated, originate from it. Notably, when establishing a money laundering offense, it is not obligatory to establish the underlying crime first. This underscores the inherent association between money laundering and its predicate crime. This study aims to advance our comprehension of legal certainty in proving money laundering when corruption serves as the underlying offense. Furthermore, it seeks to delve deeper into the notion of ideal evidence in cases where corruption acts as the predicate crime. Employing a qualitative approach with a normative juridical perspective, the research findings reveal that Indonesia has chosen a strategy of limited and balanced reverse evidence, rather than pure or absolute reverse evidence, to protect the rights of defendants. In the context of substantiating money laundering offenses, substantial and comprehensive reforms are imperative to streamline the evidentiary process, thus ensuring legal certainty. The prompt enactment of the Draft Law on Asset Confiscation is crucial to bolster the effectiveness of law enforcement agencies in combating money laundering in Indonesia. This legislation would encompass the confiscation of assets stemming from money laundering crimes, thereby facilitating a more efficient law enforcement procedure. Abstrak Tindak pidana pencucian uang pada hakikatnya ada kaitannya dengan tindak pidana yang telah terjadi sebelumnya, yang dikenal sebagai tindak pidana asal, karena harta kekayaan yang terlibat, baik ditempatkan, dialihkan, atau disatukan, berasal dari tindak pidana tersebut. Khususnya, ketika menetapkan suatu tindak pidana pencucian uang, tidak wajib untuk menetapkan terlebih dahulu kejahatan yang mendasarinya. Hal ini menggarisbawahi hubungan yang melekat antara pencucian uang dan kejahatan asal. Kajian ini bertujuan untuk meningkatkan pemahaman kita mengenai kepastian hukum dalam membuktikan pencucian uang ketika korupsi menjadi pelanggaran utama. Lebih lanjut, tulisan ini berupaya menggali lebih dalam pengertian alat bukti ideal dalam kasus-kasus dimana korupsi merupakan tindak pidana asal. Dengan menggunakan pendekatan kualitatif dan berperspektif yuridis normatif, temuan penelitian menunjukkan bahwa Indonesia memilih strategi pembuktian terbalik yang terbatas dan seimbang, dibandingkan pembuktian terbalik yang murni atau mutlak, untuk melindungi hak-hak terdakwa. Dalam konteks pembuktian tindak pidana pencucian uang, reformasi yang substansial dan komprehensif sangat penting untuk menyederhanakan proses pembuktian, sehingga menjamin kepastian hukum. Pengesahan RUU Perampasan Aset yang cepat sangat penting untuk meningkatkan efektivitas lembaga penegak hukum dalam memerangi pencucian uang di Indonesia. Undang-undang ini akan mencakup penyitaan aset yang berasal dari kejahatan pencucian uang, sehingga memfasilitasi prosedur penegakan hukum yang lebih efisien. Kata kunci: Kepastian Hukum, Barang Bukti, Korupsi, Pencucian Uang, Kejahatan AsaL